Climate-Relevant Ocean Transport Measurements in the Atlantic and Arctic Oceans - Barbara Berx; Denis Volkov; Johanna Baehr; Molly Baringer; Peter Brandt; Kristin Burmeister; Stuart Cunningham; Marieke de Jong; Laura de Steur; Shenfu Dong; Eleanor Frajka-Williams; Gustavo Goni; et al. (Oceanography, 2021)

Remote climate forcing of decadal‐scale regime shifts in Northwest Atlantic shelf ecosystems - Charles H. Greene; Erin Meyer-Gutbrod; Bruce C. Monger; Louise P. McGarry; Andrew J. Pershing; Igor M. Belkin; Paula S. Fratantoni; David G. Mountain; Robert S. Pickart; Andrey Proshutinsky; Rubao Ji; James J. Bisagni; et al. (Limnology and Oceanography, 2013)
Decadal‐scale regime shifts in Northwest Atlantic shelf ecosystems can be remotely forced by climate‐associated atmosphere‐ocean interactions in the North Atlantic and Arctic Ocean Basins. This remote climate forcing is mediated primarily by basin‐ and hemispheric‐scale changes in ocean circulation. We review and synthesize results from process‐oriented field studies and retrospective analyses of time‐series data to document the linkages between climate, ocean circulation, and ecosystem dynamics. Bottom‐up forcing associated with climate plays a prominent role in the dynamics of these ecosystems, comparable in importance to that of top‐down forcing associated with commercial fishing. A broad perspective, one encompassing the effects of basin‐ and hemispheric‐scale climate processes on marine ecosystems, will be critical to the sustainable management of marine living resources in the Northwest Atlantic.

The Rapid Response of the Canada Basin to Climate Forcing: From Bellwether to Alarm Bells - Fiona McLaughlin; Eddy Carmack; Andrey Proshutinsky; Richard Krishfield; Christopher Guay; Michiyo Yamamoto-Kawai; Jennifer Jackson; Bill Williams (Oceanography, 2011)

The Ice-Tethered Profiler: Argo of the Arctic - John Toole; Richard Krishfield; Mary-Louise Timmermans; Andrey Proshutinsky (Oceanography, 2011)

Recent Advances in Arctic Ocean Studies Employing Models from the Arctic Ocean Model Intercomparison Project - Andrey Proshutinsky; Yevgeny Aksenov; Jaclyn Clement Kinney; Rüdiger Gerdes; Elena Golubeva; David Holland; Greg Holloway; Alexandra Jahn; Mark Johnson; Ekaterina Popova; Mike Steele; Eiji Watanabe (Oceanography, 2011)